2023
DOI: 10.2147/prbm.s394787
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Daily Living and Depression in Chinese Elderly of Nursing Homes: A Mediation Analysis

Abstract: Purpose This study aimed to explore the role of sleep quality as a mediator in the activities of daily living (ADLs) and depression. Patients and Methods Participants (N=645; age≥60) were included in six nursing homes in Weifang, Shandong Province, using convenience sampling. Participants completed questionnaires to assess sleep quality, ADLs, and depression. Depression condition was assessed by the Patient Health Questionnaire (PHQ-9), ADLs was assessed by the Barthel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Studies have showed that in comparison with normal sleep duration (7–9 h for adults), either short and long sleep duration had potential to raise the risk of depression ( 26 ). Sufficient sleep duration can assist older people in performing both physical and psychological functions adequately ( 27 ). Thus, sleep duration may play a moderating role between ADL and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed that in comparison with normal sleep duration (7–9 h for adults), either short and long sleep duration had potential to raise the risk of depression ( 26 ). Sufficient sleep duration can assist older people in performing both physical and psychological functions adequately ( 27 ). Thus, sleep duration may play a moderating role between ADL and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have showed that in comparison with normal sleep duration (7-9 h for adults), either short and long sleep duration had potential to raise the risk of depression (26). Sufficient sleep duration can assist older people in performing both physical and psychological functions adequately (27). Thus, sleep duration may play a moderating role between ADL and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%